Persepsi Generasi Z terhadap Literasi Membaca di Era Digital: Preferensi terhadap Media Cetak dan Digital - Adi Wisnu Wirayuda; Gagah Rizki Maulana; Muhammad Toti Afriyanto; Riskha Afriyanti; Hesti Muliawati (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
Reading literacy in the digital era has become increasingly complex due to the overwhelming and often unstructured flow of information. Literacy does not develop automatically; instead, it requires deliberate efforts to foster reading interest to become a sustainable habit that supports knowledge acquisition, attitude formation, and skill development. This study aims to investigate Generation Z’s preferences, habits, and perceptions regarding the use of print and digital media, and how these media contribute to fostering reading interest. The research employed a qualitative method with data collected through an online questionnaire distributed to Generation Z students in the Ciayumajakuning region. The results reveal that while print media remains relevant for a portion of Generation Z, digital media has emerged as the dominant medium in cultivating their reading motivation and habits. Respondents highlighted print's sensory and credibility values, but emphasized the accessibility, interactivity, and variety of digital platforms as more appealing. The findings suggest that Generation Z demonstrates stronger engagement when reading materials are presented digitally. However, print media remains important in supporting deeper concentration and comprehension. This study implies that digital and print media should be integrated strategically in educational and social contexts to enhance literacy development. The study contributes to ongoing discussions on designing hybrid literacy strategies that combine the strengths of both media ecosystems to foster lifelong reading interest among Generation Z.